Molecular Orbital Theory-Teaching a Difficult Chemistry Topic Using a CSCL Approach in a First-Year University Course - David Johannes Hauck; Insa Melle; Andreas Steffen (MDPI AG, 2021)
Collaboration is regarded as one of the core competences of the 21st century when it comes to complex problem solving. In response to high dropout rates among STEM students, we developed a digital-collaborative intervention on a difficult topic, MO theory, for first-year chemistry students. First, students work independently in a Digital Learning Environment (DLE). Afterwards, they collaborate in small groups and create Concept Maps on MO theory. We evaluate this intervention through knowledge tests, tests of attractiveness, cognitive load, and usability during the DLE and concept mapping process, as well as audio and screen recordings during the collaborative group processes. This paper presents the detailed study design together with results from a first study in January 2021, focusing on the practicability of the intervention and students' feedback. Overall, each small group succeeded in creating a Concept Map. Students rated all phases of the intervention as attractive, with high usability and low cognitive load, although the interactive videos scored better for attractiveness and usability than the concept mapping process. On that basis, first adjustments for a second cycle of the intervention, which will be conducted in January 2022, were derived.